The connectivist design studio - Petrova, Miroslava (Design and Technology Education: An International Journal, 2021)
The design studio is the core element in the design curriculum where students gain key knowledge and skills. Typically implementing a project-based approach, it is characterised by learning by doing, collaborative learning and a prominent studio culture. The traditional notion is that the social domain of the studio has a counterpart in the physical environment. However, with the pervasion of information and communication technologies, the design studio was inevitably transferred to the digital realm. When the traditional face-to-face studio had to be transferred to an online modality enforced by covid-19 pandemics, re-conceptualization of the structure was required in order to ensure the quality of the teaching and students’ satisfaction. Based on the premise that the contents should not be simply adapted to an online version but an entirely new learning experience should be created, the redesign of the class was inspired by the principles of connectivism (Siemens, 2005). Connectivism as an alternative learning theory recognizes the societal shifts and the impact of technology on the learning processes. This new framework for understanding learning, states that knowledge is derived externally of the individual through a process of connecting nodes and patterns recognition. The paper explores the potential of connectivism applied in two online design studios at the University of Monterrey, Mexico. It describes the structure of the course and the results obtained in the online learning environment. The outcomes are verified in a survey on the perceptions of the students about their satisfaction and the effectiveness of their knowledge acquisition.